2002
DOI: 10.1002/zoo.10054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Artificial Ultraviolet Light Exposure on Reproductive Success of the Female Panther Chameleon (Furcifer pardalis) in Captivity

Abstract: Having previously documented experimentally the need for ultraviolet B (UVB) irradiation (290-315 nm) in the light environment of captive female panther chameleons (Furcifer pardalis) to ensure hatching success of their eggs, we investigated optimal UVB irradiation levels. From 1996-1998 28 hatchling female panther chameleons were raised to maturity and bred (using vitamin and mineralfortified insect diets low in vitamin D) in nine different artificial UVB light environments. Seven of the environments included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…In a study of panther chameleons [Ferguson et al, 2002], neonate females were raised through maturity and reproduction under different enforced daily UVB levels. Their reproductive success was measured in terms of the number of second-generation hatchlings produced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of panther chameleons [Ferguson et al, 2002], neonate females were raised through maturity and reproduction under different enforced daily UVB levels. Their reproductive success was measured in terms of the number of second-generation hatchlings produced.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, high doses of UVB, given a light source with similar spectral power distribution (SPD) to sunlight, do not cause excess vitamin D 3 and the associated toxic effects, because biologically inert photoproducts are produced in the skin with higher UVB exposures [Webb et al, 1989;Holick, 2004]. Optimum levels of UVB or Vitamin D are largely unknown for most species [but see Ferguson et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies of the relationship of the in vitro vitamin D-synthesizing potential of a UVB source to organismic processes, such as growth and reproduction in exotic species, are called for and may have practical applications. For example, Ferguson et al [2002] reported that UVB irradiation resulting in 0.52 to 1.32% ampule conversion to photoproducts after a 2-hr exposure resulted in viable eggs in the panther chameleon. This occurred when the exposure to the source continued for 12 hr per day and the daily intake of dietary vitamin D was negligible; conversion percentages below or greater than these values significantly reduced hatchability.…”
Section: Discussionmentioning
confidence: 97%
“…The currently available Model DMX from Spectronics Corp. (Westbury, NY), has a resolution of 10 mW/cm 2 and may not be able to adequately differentiate among irradiance levels from low wattage lamps. The older model (DM-300N), which did measure at the desired resolution, is no longer available, but literature reporting baseline data using this meter exist [Gehrmann, 1987;Ferguson et al, 2002Ferguson et al, , 2003. Most broadband radiometers tend to underestimate the actual irradiance within a band because they progressively undervalue the irradiances toward the two boundaries of the band.…”
Section: Introductionmentioning
confidence: 97%